The Impact of rs3762271 and rs930557 Polymorphisms of ASPM and MCPH1 Genes on the Anatomy and Function of the Brain. (July 2016) - Pierzak-Sominka, Joanna; Skonieczna-Żydecka, Karolina; Rudnicki, Jacek; Karakiewicz, Beata
The ASPM and MCPH 1 genes are involved in early neurogenesis and are thus potential candidates for affecting the formation of the anatomical and functional characteristics of the brain. However, the results of studies to date have been conflicting, an issue for which the factor of ethnicity may be responsible. We aimed to examine whether the rs3762271 and rs930557 polymorphisms of these two genes can influence brain anatomy and function. We enrolled 97 Caucasian neonates, with males predominating (53.6%). The anatomy of the brain was examined using ultrasound, while Doppler ultrasound was used to establish the blood flow indices in particular brain blood vessels. Genetic analysis was carried out using the polymerase chain reaction–restriction fragment length polymorphism method. The CC and AA homozygotes of rs3762271 were more common in males. The CC genotype of rs3762271 was significantly associated with birth weight ( p RE = .03) and body length ( p RE = .02). One mutant allele of rs3762271 was significantly associated with higher values of maximum ( V max, p = .04), minimum ( V min, p = .04), and average ( V mean, p = .02) speed in the pericallosal artery in newborns of both genders. Similar relationships were found in females only ( V max p = .03, V mean p = .02). The CC genotype of rs930557 was more frequently observed in male infants, but no impact on any anthropometric indices or anatomical and functional parameters of the brain was established. The ASPM gene may play a role in shaping the functional parameters of the brain in Caucasians.